Polyamines Interaction with Gaseous Signaling Molecules for Resilience Against Drought and Heat Stress in Plants - Nidhi; Noushina Iqbal; Nafees A. Khan (Plants)
Plants face a range of environmental stresses, such as heat and drought, that significantly reduce their growth, development, and yield. Plants have developed complex signaling networks to regulate physiological processes and improve their ability to withstand stress. The key regulators of plant stress responses include polyamines (PAs) and gaseous signaling molecules (GSM), such as hydrogen sulfide (H2S), nitric oxide (NO), methane (CH4), carbon monoxide (CO), carbon dioxide (CO2), and ethylene (ET). The functions of PAs and GSM in stress perception, signal transduction, and stress-responsive pathways have been explored. However, there is a lack of detailed, updated information on the interaction of PAs and GSM in the adaptation of drought and heat stress. This review explores the interaction between PAs and GSM for the adaptation to drought and heat stress. It explores their synergistic effects in mitigating the negative impacts of drought and heat stress on plant growth, development, and productivity. Moreover, a comprehensive analysis of physiological, biochemical, and molecular approaches demonstrates that their interaction activates key stress-responsive pathways, enhances antioxidant systems, and modulates gene expression. These combined effects contribute to improved drought and heat tolerance in plants. The information presented in the review provides valuable insights into plant stress resilience strategies and suggests potential measures for developing climate-resilient crops to address the increasing environmental challenges.